Eksplorasi Teritorialitas dan Personalisasi Ruang di Asrama Siswa Semi-Militer: Analisis Perbedaan Faktor Personal Antar Angkatan - Aisyah, Maghfiroh Nur; Wahyudie, Prasetyo; Astuti, Susy Budi (CV. Green Publisher Indonesia, 2025)
Territoriality is a concept that describes how individuals or groups utilize and control physical space to establish identity, ownership, and a sense of security. In the context of semi-military boarding school dormitories, which are characterized by structure and strict discipline, territoriality and space personalization serve as important means for students to express themselves and adapt socially. This study aims to explore students’ territoriality and personalization of space in semi-military boarding school dormitories, focusing on an analysis of inter-cohort differences in personal factors that influence space organization and usage. Territoriality refers to the students’ claims over space as a form of self-expression and a way to create a sense of security, while personalization involves decoration and the arrangement of personal belongings to enhance ownership, group belonging, and emotional well-being. This study employs a qualitative method combined with field observation to obtain empirical insights. The study found that students’ awareness of privacy and spatial control increased with their cohort level, shaping distinct territorial behaviors and personalization patterns.